Analysis of Factors Affecting Nurse's Skills in the Management of Infusation at Rumah Sakit Haji Medan 2021 - Upi Lestari; Asriwati; Miskah Afriani (Pena Cendekia Insani, 2022)
Health workers who are an element of health resources also have an obligation to carry out their service duties professionally. The initial survey at Haji Medan Hospital, Tembung District, showed that the number of inpatients who underwent infusion in the last 4 months was 2,185 patients and 8 (0.5%). The research design used an analytical survey research method (analytic research) with a cross sectional approach. The population in this study were 226 patients who were given intravenous infusion. The sample used a cluster random sampling system of 144 patients. Data analysis used univariate, bivariate and multivariate analysis. The results showed that there was an influence between knowledge variables p = 0.000, attitude p = 0.000, leadership p = 0.010, experience p = 0.000, career path p = 0.002 and years of service p = 0.000. The conclusion of this study is that there is an influence of knowledge, attitude, leadership, work design structure, experience, career path and years of service in the administration of infusion installation at Haji Medan Hospital, Tembung District. It is recommended to Medan Haji Hospital that nurses should be trained and supervised so that nurses can know the job descriptions and regulations that apply at Medan Haji Hospital correctly.